1997
DOI: 10.1090/s0002-9947-97-01762-5
|View full text |Cite
|
Sign up to set email alerts
|

On the conjecture of Birch and Swinnerton-Dyer

Abstract: Abstract. In this paper we complete Rubin's partial verification of the conjecture for a large class of elliptic curves with complex multiplication by Q( √ −7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In fact, we prove BSD(2) for many quadratic twists of general elliptic curves in [KL16]. Similar results for BSD(2) were previously only known for three quadratic twist families ( [Tia14] for the congruent number curve X 0 (32), [GA97], [CLTZ15] for X 0 (49) and [CCL16] for X 0 (36)).…”
Section: Thensupporting
confidence: 72%
“…In fact, we prove BSD(2) for many quadratic twists of general elliptic curves in [KL16]. Similar results for BSD(2) were previously only known for three quadratic twist families ( [Tia14] for the congruent number curve X 0 (32), [GA97], [CLTZ15] for X 0 (49) and [CCL16] for X 0 (36)).…”
Section: Thensupporting
confidence: 72%
“…Coates et al [3] [2], and Gonzalez-Avilés [16] showed that there is a large class of explicit quadratic twists of X 0 (49) whose complex L-series does not vanish at s = 1, and for which the full Birch and Swinnerton-Dyer conjecture is valid. The deep results by Skinner-Urban [30] allow (in practice, see section 3 for instance) to establish the full version of the Birch and Swinnerton-Dyer conjecture for a large class of elliptic curves without CM.…”
Section: Introductionmentioning
confidence: 99%
“…When E has complex multiplication by the ring of integers of an imaginary quadratic field K and L(E, 1) is non-zero, the p-part of the Birch and Swinnerton-Dyer conjecture has been established by Rubin [27] for all primes p which do not divide the order of the group of roots of unity of K. Coates et al [5] [4], and Gonzalez-Avilés [17] showed that there is a large class of explicit quadratic twists of X 0 (49) whose complex L-series does not vanish at s = 1, and for which the full Birch and Swinnerton-Dyer conjecture is valid (covering the case p = 2 when K = Q( √ −7)). The deep results by Skinner-Urban ( [29], Theorem 2) (see also Theorem 7 in section 8.4 below) allow, in specific cases (still assuming L(E, 1) is non-zero), to establish p-part of the Birch and Swinnerton-Dyer conjecture for elliptic curves without complex multiplication for all odd primes p (see examples in section 8.4 below, and section 3 in [10]).…”
Section: Introductionmentioning
confidence: 99%